Der Markt fur̈ Zucker - Marlen Haß (German Journal of Agricultural Economics (GJAE), 2019)
– MARLEN HAß Thun̈en-Institut fur̈ Marktanalyse Bundesallee 63, 38116 Braunschweig E-Mail: marlen.hass@thuenen.de
Keywords: 330